Technological facts on Canelo (Drimys winteri Forst.) - Rodríguez, Sandra (Bosque (Valdivia), 1998)
Some basic information about properties and use of Canelo wood in Chile, compiled from the existent information on the species, is given. Results of its use in the manufacturing of particleboards and chemical pulp as well as its behaviour on drying and wood preservation are presented. Also the physical, chemical and mechanical properties of the wood are given.